Effect of Sars-CoV-2 infection on heart rate variability of young competitive athletes - Sollazzo, F.; Morra, L.; Zanotto, A.; Monti, R.; Bianco, M.; Modica, G.; Penza, V. M.; Skittel, O.; Zeppilli, P.; Palmieri, V. (Medicina dello Sport, 2023)
BACKGROUND: Sars-CoV-2 infection may lead to clinical manifestation, occasionally related to changes in the autonomic nervous system (ANS). One of the most widely used methods to assess the ANS and the sympatho-vagal balance in the clinical setting is heart rate variability (HRV). In athletes, it is useful for diagnosing impairments in performance, in recovery after acute exertion and/or a state of chronic overtraining. The aim of the study was to test for changes in HRV a population of athletes with recent Sars-CoV-2 infection and no evidence of long-COVID syndrome.